High Prevalence of Small-Fiber Neuropathy in Patients with Tarlov Cysts: Toward a More Comprehensive Clinical Understanding - Hulens M; Zajonc P; Bruyninckx F; Rasschaert R; De Mulder P; Bervoets C; Dankaerts W (Journal of Pain Research)
Mieke Hulens,1 Peter Zajonc,2 Frans Bruyninckx,3 Ricky Rasschaert,4 Peter De Mulder,5 Chris Bervoets,6– 8 Wim Dankaerts1 1Department of Rehabilitation Sciences, Musculoskeletal Rehabilitation Research Unit, Faculty of Kinesiology and Rehabilitation Sciences, University of Leuven, Leuven, Belgium; 2Pinpoint Targeting, LLC, New York City, NY, USA; 3Department of Physical Medicine & Rehabilitation, University Hospitals of Leuven, Leuven, Belgium; 4Department of Neurosurgery, AZ Rivierenland, Bornem, Belgium; 5Department of Anesthesiology and Pain Therapy, Imelda Hospital, Bonheiden, Belgium; 6Department of Neurosciences, KU Leuven, Leuven, Belgium; 7Department of Ophthalmology, University Hospitals of Leuven, Leuven, Belgium; 8Department Adult Psychiatry, University Psychiatric Center of KU Leuven, Leuven, BelgiumCorrespondence: Mieke Hulens, Department of Rehabilitation Sciences, KU Leuven, Overwegstraat 14, 3051 Sint-Joris-Weert, Leuven, Belgium, Tel +32 477 338003, Fax +32 16 329197, Email mieke.hulens@kuleuven.bePurpose: To explore the prevalence of small-fiber neuropathy (SFN) and the clinical characteristics of patients with Tarlov cysts (PTCs), focusing on symptoms related to SFN and increased cerebrospinal pressure.Patients and Methods: In this retrospective study, 126 surveys assessing symptoms in women (30– 69 years) with Tarlov cysts (TCs) ≥ 7 mm seeking treatment for chronic back, pelvic or leg pain and skin biopsy results from 75 patients assessing intraepidermal nerve fiber density (IENFD) were reviewed.Results: IENFD < 5th percentile was documented in 80% of PTCs according to the normative reference data of Collongues et al and 72% according to the worldwide dataset of Lauria et al Questionnaires revealed high incidences of neuropathic pain (80%), allodynia (76%), pain while sitting (93%), anal sphincter (11%) and urinary sphincter (66%) problems, persistent genital arousal (27%), and restless legs (54%). Autonomic dysfunctions included early satiety (41%), bladder (93%) and bowel (88%) dysfunction, increased sweating (51%), and Raynaud’s phenomenon (45%). Other symptoms potentially associated with increased cerebrospinal fluid pressure (CSFP) were headaches (57%), fatigue (86%), cognitive issues (86%), and pulsatile tinnitus (59%).Conclusion: This study revealed a high prevalence of SFN in PTCs (72– 80%). Although the TCs may not cause radicular pain in the corresponding dermatomes directly, individuals with TCs frequently report a range of symptoms that have previously been linked to symptomatic TCs, including bladder, bowel, sphincter, and sexual symptoms, as well as local pain. Additionally, seemingly unrelated symptoms, such as headaches, fatigue, cognitive difficulties, neuropathic pain localized in other parts of the body, and autonomic dysfunctions, are commonly reported. These symptoms may be associated with elevated CSFP within the nerve root sheath. Elevated pulsatile CSFP underlies the formation of TCs at the dorsal root ganglion and may gradually contribute to small-fiber dysfunction by irritating, compressing and damaging small nerve fibers within the dorsal root ganglion.Plain Language Summary: Purpose: This study focused on how common small-fiber neuropathy (SFN) is in patients with Tarlov cysts (TCs) and examined their symptoms, especially those linked to SFN and increased spinal fluid pressure.Methods: Researchers reviewed surveys from 126 women (ages 30– 69) with TCs larger than 7 mm who sought treatment for chronic back, pelvic, or leg pain. Skin biopsy results from 75 of these patients were also used to quantify small nerve fibers.Results: A reduction in nerve fiber count per mm skin, a sign of SFN, was found in 72– 80% of patients. Common symptoms included nerve pain (80%), sensitivity to touch (76%), pain while sitting (93%), bladder problems (93%), bowel issues (88%), genital arousal (27%), and restless legs (54%). Many reported headaches (57%), fatigue (86%), memory difficulties (86%), and pulsating ear noise (59%). Other symptoms included autonomic dysfunctions (problems with the body’s automatic functions), such as sweating problems (51%), and circulation issues like Raynaud’s phenomenon (45%).Conclusion: Most patients with TCs show signs of SFN and report various symptoms, including bladder, bowel, and sexual issues, as well as widespread nerve pain and other problems like fatigue and cognitive issues. These symptoms may be caused by increased spinal fluid pressure, which stretches the nerve coverings to form Tarlov cysts and also damages small nerves in the spinal canal. Over time, this pressure could lead to SFN.Keywords: intracranial hypertension, neuropathic pain, meningeal cysts, dysautonomia, hEDS, PGAD